2002
DOI: 10.1002/ajmg.a.10846
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal fragility in patients with triple A syndrome

Abstract: Triple A syndrome is a rare, autosomal recessive disorder characterized by alacrima, achalasia, and adrenal insufficiency. Previous studies have shown that the triple A gene (AAAS) maps to chromosomal band 12q13. Mutations in the AAAS gene have been identified in triple A syndrome patients; however, the function of this gene is still obscure. We used classical and high-resolution chromosome analyses along with chromosome painting and DNA sequencing to study patients with triple A syndrome. We observed abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Cronshaw et al recently showed that nuclei, NPCs, and the nuclear envelope appear morphologically normal (21). In this respect it is noteworthy that Reshmi-Skarja et al (14) recently described chromosomal fragility with chromosomal rearrangements involving a fragile heterochromatic region (9q12) in patients with triple A syndrome. As described by Cronshaw and Matunis (21), there is only one natural ALADIN mutant (Q15K) at the N-terminus of the protein that still localizes to NPC, suggesting that this residue may be involved in an interaction with other proteins essential for ALADIN function, but not involved in NPC localization.…”
Section: Discussionmentioning
confidence: 99%
“…Cronshaw et al recently showed that nuclei, NPCs, and the nuclear envelope appear morphologically normal (21). In this respect it is noteworthy that Reshmi-Skarja et al (14) recently described chromosomal fragility with chromosomal rearrangements involving a fragile heterochromatic region (9q12) in patients with triple A syndrome. As described by Cronshaw and Matunis (21), there is only one natural ALADIN mutant (Q15K) at the N-terminus of the protein that still localizes to NPC, suggesting that this residue may be involved in an interaction with other proteins essential for ALADIN function, but not involved in NPC localization.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of mutations scattered through the AAAS gene have been reported in patients with triple A syndrome [23,24,25,26], resulting in a loss of function in the encoded ALADIN protein. Interestingly, there is considerable clinical variability among patients with the same genetic defect [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Because Sat III transcripts are stable transcripts that remain associated with the 9q12 regions even through the G2/M transition , one can speculate that long Sat III RNAs may be involved in a similar process. Finally, it has been suggested that Sat III RNAs may have a role in stabilizing chromosomal regions that are prone to instability and rearrangements (Bartlett et al 1988;Lamszus et al 1999; reviewed in Robertson andWolffe 2000 andin Duker 2002;Reshmi-Skarja et al 2003) (Fig. 2B).…”
Section: Molecular Traps For Transcription and Splicing Factors?mentioning
confidence: 99%